Automatic measurement of impedance in superionic materials using high speed (DAS) card / Anizah Hassan - Hassan, Anizah (1998)
Tbis thesis describes the automatic measurement of impedance in Superionic Materials using high speed data acquisition (DAS) card PCL 1800. The plug in DAS card is installed in the IBM Personal Computer. A series electrolyte battery-cell resistor circuit is chosen as a sample for the impedance and phase shift measurement. The impedance and phase shift measurement have been conducted using two techniques; Lissajous method for the automatic measurement and RC -circuit method for the manual measurement. A control software has been designed to automate the measurement process which was written in Visual Basic 5. The software reads the data obtained from the series electrolyte battery cell- resistor circuits, calculates the real and imaginary part of the impedance and displays the impedance response graph.